Balanced Motions Realization for a Mechanical Regulators Free and Front-Wheel Drive Bicycle Robot Under Zero Forward Speed. (29th August 2013) - Huang, Yonghua; Liao, Qizheng; Guo, Lei; Wei, Shimin
This paper focuses on a mechanical regulator free and front- wheel drive bicycle robot. We present a scheme to achieve the robot's track-stand motion and circular motion under zero forward speed. In a situation where the robot's front-bar is locked at 90 degrees, a kinetic constraint about the rotating rate of the front-wheel and the yawing rate of the frame is derived. Using the constraint as a basis, we developed a simplified model of two independent velocities for the robot. The model suggests there is an under-actuated rolling angle in the system. Our control strategy originates from the under- actuated characteristics of the robot system. Concretely, we linearize the rolling angle of the frame and set the bicycle robot to regulate its tilting by rotating the front-wheel. In the track-stand motion, we control the position and the rotational rate of the front-wheel; but in the circular motion, only the rotational rate of the front-wheel is strictly regulated. Both simulations and physical experiments results show that our strategy is effective for achieving these two motions.